Form and Meaning in Music: Revisiting the Affective Character of the Major and Minor Modes. Issue 3 (2nd October 2018) - Justus, Timothy; Gabriel, Laura; Pfaff, Adela
ABSTRACT: Musical systems develop associations over time between aspects of musical form and concepts from outside of the music. Experienced listeners internalize these connotations, such that the formal elements bring to mind their extra-musical meanings. An example of musical form-meaning mapping is the association that Western listeners have between the major and minor modes and happiness and sadness, respectively. We revisit the emotional semantics of musical mode in a study of 44 American participants (musicians and non-musicians) who each evaluated the relatedness of 96 melody-word pairs. Among the tonal melodies, we manipulated mode (major and minor) and timbre (clarinet and flute) while systematically controlling for other musical factors including pitch register and melodic contour. Similarly, among the English words, we manipulated word affect (happy and sad) while systematically controlling for other lexical factors including frequency and word length. Results demonstrated that participants provided a higher proportion of related responses for major melodies paired with happy words and minor melodies paired with sad words than for the reverse pairings. This interaction between mode and word affect was highly significant for both musicians and non-musicians, albeit with a larger effect for the former group. Further interactions with timbre suggested that while both clarinet and flute conveyed happiness when in the major mode, the clarinet was somewhat more successful than the flute at conveying sadness in the minor mode. Debriefing questionnaires suggested that the majority of the participants, including all of the non-musicians, had no awareness of the major-minor manipulation, and instead directed their attention to register and contour. We argue that the affective character of the major and minor modes is but one example of form-meaning mapping in music, and suggest further exploration of the roles of timbre, register, and contour in conveying musical emotions.